2013
DOI: 10.1007/s12031-013-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Saturated Free Fatty Acid Palmitate Alters BV-2 Microglia Inflammatory Response

Abstract: Elevated levels of free fatty acids (FFAs) in plasma and increased incidence of chronic systemic inflammation are associated with obesity. In the brain, activated microglia are believed to play different roles during inflammation that may either be neuroprotective or promote neurodegeneration. Here, we have investigated the effects of FFAs on microglial response to inflammatory stimuli. Our results indicate that the saturated FFA palmitate on its own induces alternative activation of BV-2 microglia cells. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…Despite the differential levels of TNFα mRNA in the BV-2 microglia treated with palmitate for 4 and 24 h, co-culturing with mHypoE-46 hypothalamic neurons resulted in a similar trend towards a decrease in TNFα mRNA in the neurons. The decrease in the mRNA of TNFα, a potent pro-inflammatory marker, in the mHypoE-46 neurons may indicate an anti-inflammatory effect of the BV-2 microglia by alternative activation, as previously suggested [20, 21]. The neuroprotective potential of microglia has also been shown in co- culture models with dopaminergic neurons [63], but the influence of microglia on palmitate-mediated neuroinflammation remains controversial.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite the differential levels of TNFα mRNA in the BV-2 microglia treated with palmitate for 4 and 24 h, co-culturing with mHypoE-46 hypothalamic neurons resulted in a similar trend towards a decrease in TNFα mRNA in the neurons. The decrease in the mRNA of TNFα, a potent pro-inflammatory marker, in the mHypoE-46 neurons may indicate an anti-inflammatory effect of the BV-2 microglia by alternative activation, as previously suggested [20, 21]. The neuroprotective potential of microglia has also been shown in co- culture models with dopaminergic neurons [63], but the influence of microglia on palmitate-mediated neuroinflammation remains controversial.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have suggested that microglia are the essential players in the increased expression of inflammatory cytokines that leads to neurotoxicity in a high-fat environment [19]. On the contrary, other studies have shown that palmitate may induce an alternative, anti-inflammatory response in microglia, resulting in neuroprotection [20, 21]. It is likely that both are possible given the temporal responses necessary for resolution of an acute inflammatory response versus the chronic neuroinflammation seen with long-term exposure to high fat [22].…”
Section: Introductionmentioning
confidence: 99%
“…FFA can stimulate vascular smooth muscle proliferation and induce endothelial dysfunction, which may contribute to the cardiovascular events of NAFLD48. Furthermore, FFA have been implicated in the physiological mechanism of cardiovascular disease resulting from low-grade systemic inflammatory processes4950. On the basis of our study, we can only propose a role of FFA in the aetiology of NAFLD and inflammation from a snapshot of the circulating FFA state.…”
Section: Discussionmentioning
confidence: 77%
“…28 Longer chain saturated fatty acids have the ability to upregulate activation of macrophages/microglia via promotion of toll-like receptor signalling and by supporting ceramide synthesis. [29][30][31][32] Conceivably, this helps to rationalise the many epidemiological studies associating metabolic syndrome and long-chain saturate-rich diets with increased risk for neurodegenerative disorders and atherogenesis. 33 34 Although MCFAs cannot give rise to palmitate and have not promoted macrophage activation in some studies, other researchers report that, especially under low-serum conditions, LA can activate macrophages by promoting signalling via certain toll-like receptors-TLR2 heterodimers and TLR4 homodimers.…”
Section: Health Advantages Of Medium-chain Fatty Acidsmentioning
confidence: 99%